DAMPAK PEMBERIAN TUNJANGAN DAN MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN DI SEKTOR PERBANKAN CABANG DI JAKARTA SELATAN (Faletehan Jurnal Ekonomi dan Bisnis, 2024)
This research aims to determine the influence of allowances and work motivation on the performance improvement of employees in the Banking sector at the South Jakarta Branch. The type of research conducted is explanatory, with data collection using a questionnaire, and the sampling technique employed is saturated sampling with a sample size of 55 employees. The analysis method utilized is quantitative analysis. The partial test results indicate a positive and significant influence of allowances on employee performance, and work motivation has a positive and significant effect on employee performance. Additionally, both allowances and work motivation simultaneously have a positive and significant impact on employee performance..